HEMODYNAMIC STABILITY AND RECOVERY TIME OF PROPOFOL AND SEVOFLURANE IN ULIN GENERAL HOSPITAL BANJARMASIN - Lesiana, Rina; Sikumbang, Kenanga Marwan; Istiana, Istiana; Susianto, Oky; Wydiamala, Erida (Fakultas Kedokteran Universitas Lambung Mangkurat, 2017)
Abstract: The main interest in general anesthesia is safety and the well being of the patient especially the stability of hemodynamic during induction until extubation. The most common causes of prolonging awakening are residual effects of drugs either anesthetics, sedatives, and analgesics. This study aimed to compare hemodynamic stability and recovery time between propofol and sevoflurane at Ulin General Hospital Banjarmasin. This was an observational analytic study conducted in July until November 2016 on 31 patients. The result showed that mean systolic blood pressure, diastolic blood pressure and heart rate for 90 minutes maintenance were no significant difference in group-A (propofol) compare with group-B (sevoflurane), post hoc Bonferroni test showing p>0.05. Mean recovery time to consciousness was faster in group-A (10,46 minutes) than group-B (15,59 minutes), there was no significant difference in two group. In conclusion, there was no significant difference in hemodynamic stability and recovery time between propofol and sevoflurane.Â Keywords: hemodynamic stability, recovery time, propofol, sevoflurane.